The old age and the sport like object of social representations - Luis Javier Ruiz Cazorla; José Luis Chinchilla Minguet; Manuel Ruiz Cazorla (FEADEF, 2010)
In the present work we analyzed the social function of the Physical Education and the sport with respect to the elderly people. One is a relation hyped by the social representations that the implied agents own on the old age, the body, the health and the sport, nonfree of stereotypes and prejudices that condition their social practices. It constitutes a social problem and simultaneously a challenge for institutions to eradicate the social practices of exclusion to that they give rise. For it two steps are essential. In the first place to denounce the contents of the social representations on the sport old age and activities physical that favor the social exclusion, especially from the Educative System and mass media. Secondly to promote the average materials and necessary structural conditions for the social change.